2013
DOI: 10.1103/physreva.87.053624
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear quantum piston for the controlled generation of vortex rings and soliton trains

Abstract: We propose a simple way to generate nonlinear excitations in a controllable way by managing interactions in Bose-Einstein condensates. Under the action of a quantum analogue of a classical piston the condensed atoms are pushed through the trap generating vortex rings in a fully threedimensional condensates or soliton trains in quasi-one dimensional scenarios. The vortex rings form due to transverse instability of the shock wave train enhanced and supported by the energy transfer between waves. We elucidate in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 69 publications
0
46
0
2
Order By: Relevance
“…Though this implies that the formation mechanism of the petal structure can be understood in terms of linear physics, the condensate itself and each of its lobes still represent a highly nonlinear system due to polaritonpolariton interactions. Arrays of the lobes represent excitations of the condensate ground state and can arise due to the interaction of counterpropagating superfluids in an effective 1D setting (36,37). We assume that the reported ring condensates occupy excited states instead of their ground states to maintain energy conservation: polaritons generated in the blue-shifted pumping regions that scatter into the condensate lack an efficient mechanism for energy relaxation (28)…”
Section: Theoretical Descriptionmentioning
confidence: 99%
“…Though this implies that the formation mechanism of the petal structure can be understood in terms of linear physics, the condensate itself and each of its lobes still represent a highly nonlinear system due to polaritonpolariton interactions. Arrays of the lobes represent excitations of the condensate ground state and can arise due to the interaction of counterpropagating superfluids in an effective 1D setting (36,37). We assume that the reported ring condensates occupy excited states instead of their ground states to maintain energy conservation: polaritons generated in the blue-shifted pumping regions that scatter into the condensate lack an efficient mechanism for energy relaxation (28)…”
Section: Theoretical Descriptionmentioning
confidence: 99%
“…Optical Feshbach resonances, however, have been shown to allow fine spatial control of the scattering length and recent experimental results show modulations of the s-wave scattering length on the scale of hundreds of nanometers [32]. Furthermore, it has been shown that the collisionally inhomogeneous regime supports a plethora of new nonlinear phenomena such as the adiabatic compression of matter-waves [28,33], Bloch oscillations of matter-wave solitons [28], atomic soliton emission and atom lasers [34], dynamical trapping of matter-wave solitons [35][36][37][38][39], enhancement of transmissivity of matter-waves through barriers [35,36,40], formation of stable condensates exhibiting both attractive and repulsive interatomic interactions [41][42][43], the delocalization transition in optical lattices [44], spontaneous symmetry breaking in a nonlinear double-well pseudopotential [45], the competition between incommensurable linear and nonlinear lattices [36,46], the generation of solitons [47,48] and vortex rings [49], and many others.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental schemes for creating vortex rings in atomic Bose-Einstein condensates (BECs), based on dynamical instabilities of collective excitations [3] or condensate collisions [4,5], have been successfully tested. Additional theoretical proposals involve collisions of two-component BECs with different velocities [6], space-dependent Feshbach resonance [7], or phase imprinting methods [8].…”
mentioning
confidence: 99%